STUDENTS PERCEPTION ON READING COMPREHENSION PROBLEMS IN NARRATIVE TEXT - Sari, Gita Rosita; Santihastuti, Asih; Wahjuningsih, Eka (LLT Journal: A Journal on Language and Language Teaching, 2020)
This survey study aimed to know the students perception on reading comprehension problems of narrative text. The sample participants were randomly selected from the tenth grade students of SMAN 2 Jember in academic year of 2019/2020. Questionnaire adopted from Xiubo Zhang (2006) was used to collect the students perception and it was translated into Indonesian. The result showed that the students still experienced some problems in reading narrative text. Based on the result of the questionnaire, the most problematic aspect that hinder the students reading comprehension was Motivation (65.6%), followed by Strategies (63.7%), Background Knowledge (63.3%), Reading Process (60%) and Language Knowledge (55.4%). The result implied that the teacher should focus on fostering students motivation by giving intensive course and reading assignment based on the students interests. In order to see further into the problem faced by the students, future reseacher could use direct assesment by using diagnostic test or other measurement.